KEANEKARAGAMAN HERPETOFAUNA DI TAMAN NASIONAL GUNUNG HALIMUN, JAWA BARAT - Mumpuni Mumpuni (BERITA BIOLOGI, 2001)
As one of the remaining tropical rain forest and the largest conservation area in Java, Gunung Halimun National Park (GHNP) has at least 53 reptiles and amphibians where two rare endemic tree frogs Nyctixalus margaritifer and Philautus pallidipes were collected.The skink species Sphenomorphus puncticentralis has also been succesfully collected after the first and the only collection in 1979 at Baturaden,Central Java.